Chronic Liver Disease and Hepatitis-B Antigen: A Prospective Study. Issue 5928 (17th August 1974) - Van Waes, L.; Segers, J.; Van Egmond, J.; Van Nimmen, L.; Barbier, F.; Wieme, R.; Demeulenaere, L.
Abstract : A long-term follow-up of 45 patients with chronic hepatitis and 41 with cirrhosis is reported. Hepatitis-B antigen (HBAg) was present in 19 (42%) of the chronic hepatitis patients and in 20 (49%) of those with cirrhosis. The clinical course and biochemical and histological findings in the HBAg-positive and the HBAg-negative cases were similar, suggesting that HBAg-positive chronic liver disease is not a distinct clinical entity. The presence of antigen and autoantibodies was not found to be mutually exclusive. In HBAg-positive cases antigen tended to persist for months and years. When no irreversible lesions exist disappearance of the antigen may be a sign that the liver disease will resolve.